2000
DOI: 10.1128/mcb.20.20.7541-7549.2000
|View full text |Cite
|
Sign up to set email alerts
|

BRG-1 Is Recruited to Estrogen-Responsive Promoters and Cooperates with Factors Involved in Histone Acetylation

Abstract: Several factors that mediate activation by nuclear receptors also modify the chemical and structural composition of chromatin. Prominent in this diverse group is the steroid receptor coactivator 1 (SRC-1) family, which interact with agonist-bound nuclear receptors, thereby coupling them to multifunctional transcriptional coregulators such as CREB-binding protein (CBP), p300, and PCAF, all of which have potent histone acetyltransferase activity. Additionally factors including the Brahma-related gene 1 (BRG-1) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
146
2
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(162 citation statements)
references
References 48 publications
12
146
2
2
Order By: Relevance
“…Brg1 has been reported to be connected with the activation of ERα-mediated transcription (DiRenzo et al, 2000) and further it was found that prohibitin interacts with Brg1/Brm and represses ERα mediated transcription after the binding of estrogen antagonist to the ERα, by the mechanism requiring both Brg1 and Brm (Zhang et al, 2007). Research has also shown that the depletion of prohibitin using siRNA prevented tamoxifen-induced cell cycle arrest from the tamoxifen-sensitive breast cancer cells (Wang et al, 2004) exploring a powerful connection between Estrogen and Prohibitin.…”
Section: Discussionmentioning
confidence: 99%
“…Brg1 has been reported to be connected with the activation of ERα-mediated transcription (DiRenzo et al, 2000) and further it was found that prohibitin interacts with Brg1/Brm and represses ERα mediated transcription after the binding of estrogen antagonist to the ERα, by the mechanism requiring both Brg1 and Brm (Zhang et al, 2007). Research has also shown that the depletion of prohibitin using siRNA prevented tamoxifen-induced cell cycle arrest from the tamoxifen-sensitive breast cancer cells (Wang et al, 2004) exploring a powerful connection between Estrogen and Prohibitin.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin immunoprecipitation experiments have demonstrated the presence of hSWI/SNF components on the promoters of IFNgand IFNa-inducible genes, as well as on the IFNb promoter (Agalioti et al, 2000;Huang et al, 2002;Liu et al, 2002;Pattenden et al, 2002;Cui et al, 2004). hSWI/SNF is also present on the CD44 and E-cadherin promoters (Banine et al, 2005;Gresh et al, 2005), on the promoters for myogenin and muscle creatine kinase (Simone et al, 2004), and on steroid receptor targets (Fryer and Archer, 1998;DiRenzo et al, 2000;Belandia et al, 2002;Me´tivier et al, 2003;Link et al, 2005). Despite the growing knowledge of promoters regulated by hSWI/SNF, it is not well understood how the complex becomes localized and activated at various promoters; however, there is evidence for the involvement of signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The chromatin remodeling ability of hSWI/SNF has been shown to respond to various signaling pathways, including response to phosphoinositols (Zhao et al, 1998;Rando et al, 2002), the p38 pathway during skeletal myogenesis (Simone et al, 2004), interferons (Agalioti et al, 2000;Huang et al, 2002;Liu et al, 2002;Cui et al, 2004) and nuclear hormone receptors (Fryer and Archer, 1998;DiRenzo et al, 2000;Belandia et al, 2002;Me´tivier et al, 2003;Link et al, 2005). Phosphatidyl inositol 4,5-bisphosphate (PIP 2 ) has been shown to help increase the association of the SWI/SNF complex with the nuclear matrix (Zhao et al, 1998;Rando et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Human SWI/SNF is heterogeneous and known to contain either Brm or its related protein Brg1, the ATPase subunits of the complexes (Wang et al, 1996). In transient transfection and in vitro transcription assays, both hBrm and hBrg1 can facilitate transcriptional activation by glucocorticoid receptor (GR), estrogen receptor (ER), and retinoic acid receptor (RAR) (Dilworth et al, 2000;DiRenzo et al, 2000). Accumulated evidence indicates that the coactivators CARM1 and ATP-dependent chromatin remodeling factor SWI/ SNF have critical functions in transcriptional activation by nuclear receptors.…”
Section: Introductionmentioning
confidence: 99%